Total synthesis of the potent antifungal agents bengazole C and E - Enríquez-García, Álvaro; Ley, Steven V (Collection of Czechoslovak Chemical Communications, 2009)
The bengazoles are marine natural products with unique structure, containing two oxazole rings flanking a single carbon. They show very potent antifungal activity. The total syntheses of bengazole C and E are described following a convergent route which involves diastereoselective cycloaddition of an appropriately substituted nitrile oxide with a butane-1,2-diacetal-protected alkenediol as the key step.
Keywords: Porifera; Oxazoles; oxazoly; financování organizované; Financing, Organized; Antifungal Agents; antifungální látky